Prevalence of human immunodeficiency virus and hepatitis B virus infections in young women seeking abortion care in Ethiopia: a cross - sectional study. (December 2016) - Mulu, Wondemagegn; Zenebe, Yohannes; Abera, Bayeh; Yimer, Mulat; Hailu, Tadesse
Abstract Background Young women aged 15–24 years are members of key populations at higher risk for Human Immunodeficiency Virus (HIV) acquisition through sexual intercourse. In areas where unprotected sex is a common practice, Hepatitis B virus (HBV) commonly transmitted via sexual and parenteral routes. The study aimed at determining HIV and HBV infections prevalence in young women attending health institutions for abortion care in Bahir Dar city, Ethiopia. Methods A cross - sectional study was conducted from January 2015 to June 2015. Convenient sampling technique was used. Demographic and explanatory variables were collected using a structured questionnaire via face to face interview. The presence of antibody to HIV infection was detected using national HIV diagnostic test algorithm. Hepatitis B surface antigen (HBsAg) was detected using ELISA. Data were analyzed using descriptive, fisher's exact and independent sampleT test as appropriate. Results A total of 360 young women aged 15–24 years participated in the study. The median age of the women was 22 years. Overall, 16 (4.4 %) (95 % CI: 2.7–7.1 %) women were positive for either HBV or HIV infections. The prevalence of HIV and HBV infections were 9 (2.5 %) (95 % CI: 1.3–4.7 %) and 7 (1.94 %) (95 % CI: 0.95–4.0 %), respectively. The mean age of first sexual intercourse was 17.6 and 19.3 in HIV and HBV infected women, respectively. The prevalence of HIV infection was significantly associated with lower educational status (P < 0.001), divorced marital status (P = 0.009) and ever had symptom of other sexually transmitted infections (P = 0.001). The proportion of HBV was higher in women aged 15–17 years (P = 0.02). Conclusion Though there were no co-infections, HIV and HBV infections are major health problems in young women seeking abortion care. Therefore, appropriate prevention, treatment and care services must be reached to these higher risk populations.